COMPARISON EMPOWERMENT PUBLIC IN FULFILLING THE NEED FOR CLEAN WATER FOR COMMUNITY WELFARE IN GUWO VILLAGE, WONOSEGORO DISTRICT AND GARANGAN VILLAGE, WONOSAMODRO DISTRICT - Amelia Yogi Oktaviana; Rini Fidiyani Fidiyani (Universitas Negeri Semarang, 2026)
The problem of clean water availability remains a significant issue in various rural areas, including Guwo Village and Garangan Village. Based on the research results, approximately 80% of the people of Guwo Village stated that it was easy to obtain clean water, while in Garangan Village only around 65% felt this convenience, especially experiencing difficulties during the dry season. The objectives of this study are, 1. Analyze the pattern of community empowerment in fulfilling clean water needs in Boyolali Regency 2. Analyze the impact of community empowerment on fulfilling clean water needs. The research method used by this researcher uses a qualitative approach with a sociological juridical research type. The data sources used in this study are primary, secondary and tertiary data sources. The research results show that community participation in Guwo Village is high, resulting in more effective and stable clean water management. Meanwhile, in Garangan Village, community participation is still limited, resulting in unstable water availability, especially during the dry season. The impact of empowerment is evident in improved access to clean water, improved health, and improved social and economic relationships in the community. The theories in this study are 1) Marc Zimmerman's empowerment theory to explain the increase in community capacity and independence. 2) John Kingdon's policy theory to understand the role of policy in supporting clean water supply programs. These two theories are used to analyze the relationship between community participation and policy in the success of the program. The conclusions of this study are: 1) The empowerment pattern in Guwo Village is more organized, while Garangan Village is still self-sufficient. 2) Guwo community participation is higher (80%) than Garangan (60%), so management is more effective. 3) Empowerment improves access to water, health, and the socio-economic conditions of the community.